2021
DOI: 10.1021/acs.energyfuels.1c01855
|View full text |Cite
|
Sign up to set email alerts
|

A-Site Doped Perovskite Oxide Strongly Interface Coupling with Carbon Nanotubes as a Promising Bifunctional Electrocatalyst for Solid-State Zn–Air Batteries

Abstract: Constructing an effective and stable oxygen reduction reaction/oxygen evolution reaction electrocatalyst for solid-state Zn–air batteries is essential but remains challenging. In this work, carbon nanotubes were in situ grown on the surface of Sr, P-codoped LaTiO3 perovskite oxide (La0.6Sr0.4TiO3-P@CNTs) through a convenient chemical vapor deposition method. Benefiting from the A-site substitution and interfacial modification engineering, the as-prepared La0.6Sr0.4TiO3-P@CNTs show promising oxygen bifunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Recently, Zeng et al ., grew carbon nanotubes on the surface of La 0.6 Sr 0.4 TiO 3 ‐P using chemical vapor deposition. Co‐doping and interfacial engineering in La 0.6 Sr 0.4 TiO 3 ‐P@CNTs resulted in excellent electrochemical activity for Zn‐Air batteries [133] . Similarly, Gui et al ., designed an integrated electrocatalyst, Ce 0.9 Gd 0.1 O 2‐δ decorated (Pr 0.5 Ba 0.5 )CoO 3‐δ perovskite for the application of Zn‐air batteries [134] .…”
Section: B‐site Cation or Cationic Substitutionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, Zeng et al ., grew carbon nanotubes on the surface of La 0.6 Sr 0.4 TiO 3 ‐P using chemical vapor deposition. Co‐doping and interfacial engineering in La 0.6 Sr 0.4 TiO 3 ‐P@CNTs resulted in excellent electrochemical activity for Zn‐Air batteries [133] . Similarly, Gui et al ., designed an integrated electrocatalyst, Ce 0.9 Gd 0.1 O 2‐δ decorated (Pr 0.5 Ba 0.5 )CoO 3‐δ perovskite for the application of Zn‐air batteries [134] .…”
Section: B‐site Cation or Cationic Substitutionmentioning
confidence: 76%
“…Co-doping and interfacial engineering in La 0.6 Sr 0.4 TiO 3 -P@CNTs resulted in excellent electrochemical activity for Zn-Air batteries. [133] Similarly, Gui et al, designed an integrated electrocatalyst, Ce 0.9 Gd 0.1 O 2-δ decorated (Pr 0.5 Ba 0.5 )CoO 3-δ perovskite for the application of Zn-air batteries. [134] Lin et al, formed a unique integrated structure of LaCoO 3 perovskite nanoparticles with micro/mesoporous nitrogen-doped carbon nanofibers by solid-liquid co-electrospinning method and reported that uniformly anchored nanoparticles on porous nanofibers resulted in increased activity.…”
Section: Composite/hybrid Structurementioning
confidence: 99%
“…Therefore, Li–air batteries require an extra-sophisticated water-proof layer to protect the anode active materials which would add to the complexity of these batteries. , Therefore, metal–air batteries other than Li–air are explored to a greater extent. In this regard, Al–air, Zn–air, and to some extent Na–air batteries (under nonaqueous) are considered as potential candidates considering their low cost owing to abundant raw materials. As far as nonaqueous batteries are concerned, a Na–air battery could provide an output energy density of about 1600 Wh kg –1 . However, both Na–air and Li–air systems use nonaqueous electrolytes because of their reactivities with air, moisture, and water.…”
Section: Organic Monolayers For Metal–air Batteriesmentioning
confidence: 99%
“…However, in selected cases, very thin monolayers can be used to stabilize the cathode–electrolyte interface in solid-state batteries. Nevertheless, a good number of high-performance bifunctional electrocatalysts have been developed for the cathode recently. ,,,, However, they cannot continue their good activity and stability if the cycle period is over 2 h at higher current density (typically ∼20 mA cm –2 or higher). A tough problem is the degradation of most OER catalysts including IrO 2 and RuO 2 catalysts, especially under high current densities.…”
Section: Organic Monolayers For Metal–air Batteriesmentioning
confidence: 99%
“…To date, most perovskite oxide composites have been reported with conductive carbon-based support materials, such as graphene, carbon black, carbon nanotubes, acetylene black, Vulcan carbon, etc. However, these carbon-based materials are not suitable for long-term stability because of the occurrence of electrochemical corrosion under a high oxidative potential, leading to a reduction in the number of active sites. However, the successful synthesis of perovskite composites with other OER active electrocatalysts encounters the difficulty of forming secondary phases and rationally controlling the composition.…”
Section: Introductionmentioning
confidence: 99%